1996
DOI: 10.1590/s0074-02761996000100022
|View full text |Cite
|
Sign up to set email alerts
|

Thermal effect on the life-cycle parameters of the medically important freshwater snail species Lymnaea (Radix) luteola (Lamarck)

Abstract: The snails Lymnaea (Radix)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The growth and survivorship of P. acuta in the present instance are more similar to the observations made on the populations of South Africa (Brackenberry, Appleton, 1993) reared at a constant temperature of 25 ˚C. The temperature-dependent variation observed in the South African population of P. acuta is similar to those observed in the two indigenous snails Lymnaea luteola and Indoplanorbis exustus (Aziz, Raut, 1996). Under laboratory culture, the snails Lymnaea luteola(1.23 mm and 18.63 mg of shell length and body weight) and Indoplanorbis exustus (0.78 mm in shell diameter and 31.2 mg body weight) exhibited higher increment (per week) than Physa acuta (0.52 mm shell length and 2.38 mg body weight), under similar temperature conditions.…”
Section: Discussionsupporting
confidence: 88%
“…The growth and survivorship of P. acuta in the present instance are more similar to the observations made on the populations of South Africa (Brackenberry, Appleton, 1993) reared at a constant temperature of 25 ˚C. The temperature-dependent variation observed in the South African population of P. acuta is similar to those observed in the two indigenous snails Lymnaea luteola and Indoplanorbis exustus (Aziz, Raut, 1996). Under laboratory culture, the snails Lymnaea luteola(1.23 mm and 18.63 mg of shell length and body weight) and Indoplanorbis exustus (0.78 mm in shell diameter and 31.2 mg body weight) exhibited higher increment (per week) than Physa acuta (0.52 mm shell length and 2.38 mg body weight), under similar temperature conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Ecology of aquatic habitats is greatly influenced by temperature (Huet,1986) by controlling the ecological characteristics of organisms as well as solubility of different gases and salts in water .Temperature recorded during the study period ranging from 16.4 ºC (in Waterbody 2,December2017) to 33.4ºC (in Waterbody 1,August2017). Aziz et al (1996) reported 20ºC -35ºC is conducive for growth and multiplication of gastropods. From the above observations it can be concluded that during the study period, temperatures of the studied waterbodies were conducive for gastropod's growth and reproduction.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was observed that the reproduction rate of Radix acuminata in the tropics occurred optimally at a temperature range of 16–34°C [ 39 , 40 ]. Furthermore, Aziz [ 42 ] and Misra [ 41 ] found that the reproduction rate of Radix luteola (Lamarck) and Radix acuminata , respectively, was higher at lower temperature ranges of 15–20°C. In subtropical regions, 5–10°C was the minimal temperature needed for Pseudosuccinea columella and Austopeplea ( Lymnaea ) tomentosa egg development and hatching [ 66 ].…”
Section: Resultsmentioning
confidence: 99%